The End of Agrarianism: The Fight for Farm Parity in Alberta and Saskatchewan, 1935-48 - Monod, David (Labour / Le Travail, 1985)
This paper deals with an attempt by the farmers of Alberta and Saskatchewan to have the economy regulated to their advantage. Through parity, the farmers hoped to have the prices of the goods they bought controlled by the values of those they had to sell. The agitation in favour of parity prices lasted ten years, and it culminated in a massive 30-day farm strike in autumn 1946. At the heart of the whole matter was the issue of agrarian survival. The struggle for parity involved marginal farmers who worked small acreages and had large overheads. These producers were being impoverished by their inability to compete with their more mechanized counterparts. The ultimate failure of their protest marked the end of the non-competitive farmers' existence in agriculture. But despite its failure, the agitation reveals not only the similarities between the industrialization process in its urban and rural contexts, but also the difficulties involved in transferring forms of dissent from one sector to the other.
Keywords: AGRARIAN societies; AGRICULTURAL economics; Agriculture; Alberta; Economic policy; FARM life; Farmers; INDUSTRIALIZATION; PARITY